U.S. - South America ocean grain freight spreads - O'Neil, Jay (Kansas State University. International Grains Program Institute, 2015)
This study highlights the market influences that affect ocean freight spreads between North and South American ports of origin to Asia and how these spreads affect the competitiveness of U.S. grain exports to Asia. Rate comparisons from the U.S. Gulf to China have been used as opposed to the U.S. Pacific Northwest (PNW) because of the limitations presented by the Panama Canal and the Canal transit costs as this is where the Atlantic freight spread competition exists.
Keywords: Grain exports; North America; South America; Asia; Costs